INCREASING THE EFFICIENCY OF BRAKING FRICTION PAIRS - Volchenko, Dmytro; Zhuravlov, Dmytro; Voznyi, Andrii; Vudvud, Oleksandr; Andreychikov, Yevhen; Vasylyshyn, Olga (Problems of Friction and Wear, 2026)
Theoretical and experimental studies of narrow friction linings with reduced working surfaces in drum-shoe brake friction pairs have revealed and applied the following.Specific loads are quasi-equalized by significantly reducing the advancing and trailing areas of the lining surfaces.The overall dynamic coefficient of mutual overlap of friction pairs during operation of narrow linings has been increased, stabilizing the temperature and gradients on their surfaces, as well as the dynamic friction coefficients.A new method for fastening narrow linings in friction units significantly reduces the time required to install and remove them from brake shoes.